Keeseckers celebrate anniversary (Raton Range Raton, New Mexico, 1977)
Newspaper Article on the 60th Anniversary of Mr. and Mrs. Earl Keesecker.
Master list item #: 86
File location is in the Raton File Cabinet
Keywords: Keesecker, Earl; Keesecker, (Mrs.); Wooten, Sue; Seward, Velma; Stoller, Norma; Gleaves, Ona; Murphy, Mable; Stevens, Jewel; MacDougall, Laura; Keesecker, Robert; Keesecker, (Mrs.); Keesecker, Angela; Carden, James; Carden, (Mrs.); Carden, Don; Rea, Eldon; Rea, (Mrs.); Julian, John; Julian, (Mrs.); Marriott, Ray; Marriott, (Mrs.); Stewert, Guy; Stewert, (Mrs.); First National Bank; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Glaveston, Texas; Wenatchee, Washington; Fairfield, Connecticut; Tacoma, Washington; Lakeside, Arizona; Denver, Colorado; Trinidad, Colorado